Gerakan 5000 Donasi Buku Dalam Upaya Membangun Budaya Literasi : Tahap 4 - Vidila Rosalina; Donny Fernando; Saefudin Saefudin; Hikmatullah Hikmatullah (CERED Indonesia Publishing, 2021)
The society of a nation has a vertical relationship to the quality of the nation. The high interest in reading someone's book influences one's insight, mentality, and behavior. The Indonesian nation is a nation with a low literacy level even though it has been 70 years since Indonesia became an independent country. There are many factors why Indonesian society's literacy has a low percentage. These problems must immediately get serious attention not only from the government but from all of us. How does the discourse about